(untitled) (TEST Ticontre. Theory Text Translation, 2021)
The character of the care worker and the phenomenon of the badantato, which is one of the most significant of the working reality of the last twenty years in Italy, are almost absent from the anthologies on work, which is problematic if we consider that the anthologies are configured as choral, plural and collective narratives, in which, therefore, the voice of the badante is silenced. The reasons can be found in the double invisibility of the badante, as care worker and as immigrant, as well as in the strong autobiographical dimension of the work’s writings and in the question of authorship. In the very scarce short stories available, we examine, by way of example, a text by Andrea Bajani and a text by Dacia Maraini.